'A stream of words' – the Antwerp Quay Poem as interrogation of urban open form, polyphony and radical dialogue. Issue 7 (3rd July 2022) - Ameel, Lieven
ABSTRACT: This article examines polyphony and open form as key concepts connecting literary theory and urban planning. It focuses on Peter Holvoet-Hanssen's Quay Poem, an in-situ poem painted in 2011 on the floodwalls of the Antwerp quays during Holvoet-Hanssen's tenure as city poet. The long poem in public space provides important insights into how literary city texts and the discourses of urban development draw ultimately on similar narrative structures, in close dialogue with past layers of urban meaning and in the shadow of future material transformations. The poem gestures also to insights planning can gain from literary forms of storytelling, in particular in the way Holvoet-Hanssen's poem produces a remarkable openness of form; in the way it articulates a radical variety of different voices; and in the way it continues to speak after the text itself has disappeared from the public built environment.